Reinterpreting a community outbreak of Salmonella enterica serotype Enteritidis in the light of molecular typing - Nastasi Antonino; Buonomini Maria; Nicoletti PierLuigi; Romani Cristina; Mammina Caterina (BMC, 2007)
Abstract Background In November 2005, a large outbreak due to Salmonella enterica serotype Enteritidis (S. Enteritidis) was observed within children who had eaten their meals at 53 school cafeterias in Florence and the surrounding area. A total of 154 isolates of S. Enteritidis were recovered from human cases between November 2005 and January 2006. All strains were assigned phage type 8 (PT8) and a common XbaI pulsotype. This paper reports the findings of a molecular epidemiological investigation performed on 124 strains of S. Enteritidis isolated in the years 2005 and 2006 in Florence and the surrounding area, including the epidemic isolates. Methods One hundred twenty-four human isolates of S. Enteritidis identified in the period January 2005 - December 2006 were submitted to molecular typing by single enzyme - amplified fragment length polymorphism (SE-AFLP). Results Molecular subtyping by SE-AFLP yielded five different profiles. In the pre-epidemic phase, type A included 78.4% of isolates, whereas only three (8.1%) belonged to type C. All isolates, but one, of the epidemic phase were indistinguishable and attributed to type C. In the post-epidemic period, a polymorphic pattern of SE-AFLP types was again recognized but type C accounted for 73.3% of the isolates during the first six months of 2006, whereas during the remaining six months type A regained the first place, including 52.0% of the isolates. Conclusion The epidemic event was attributed to the emergence and clonal expansion of a strain of S. Enteritidis PT8-SE-AFLP type C. Circulation of the epidemic clone was much more extensive than the surveillance and traditional laboratory data demonstrated.